ANALISIS KINERJA KEUANGAN SEBAGAI ALAT PREDIKSI KEBANGKRUTAN DENGAN MODEL DISKRIMINAN - Yulinartati Yulinartati (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
The purpose of this study was to determine whether the Current Ratio (CR), Debt Equity Ratio (DER), Total Assets Over Turen (TATO), net profit margin (NPM), Debt to Assets Ratio (DAR), Return on Assets (ROA) , Return on Equity (ROE), Gross Profit Margin (GPM), Operating Profit Margin (OPM) influential in distinguishing healthy firms and perusahaa bankruptcy discriminant model. Based on discriminant analysis of known groups of healthy companies and a group of companies that went bankrupt differ significantly, from 9 (nine) variables are in use only 4 (four) variable Current Ratio, Debt Equity Ratio, Net Profit Margin, and Gross Profit Margin is selected and able to differentiate healthy companies and companies go bankrupt, while the 5 (five) of the variables, Turn Over Total Assets, Debt to Assets Ratio, Return on Assets, Return on Assets, and Operating Profit Margin are not able to differentiate healthy and bankrupt companies. Keywords: Current Ratio ,Debt Equity Ratio, Total Assets Turen Over , Net profit Margin , Return on Assets, Return on Equity